2020
DOI: 10.3390/f11101086
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Consequences of Hybridization in Relict Isolated Trees Pinus sylvestris and the Pinus mugo Complex

Abstract: Scots pine (Pinus sylvestris L.) and the taxa from the P. mugo complex can hybridize in the contact zones and produce fertile hybrids. A unique example of an early Holocene relict population of P. sylvestris and P. uliginosa (a taxon from the P. mugo complex) growing on the tops of Jurassic sandstone rocks is located in Błędne Skały (Sudetes). Phenotypically, there are trees resembling P. sylvestris, P. uliginosa and intermediate forms between them. We expected that some of P. sylvestris and/or P. uliginosa-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Our data indicate that the pattern of introgression is not symmetric between taxa, and in general, stronger gene flow was estimated from representatives of the P. mugo complex to P. sylvestris than in the opposite direction. Earlier studies reported such asymmetric ongoing gene flow within present-day contact zones of P. uliginosa, P. mugo, and P. sylvestris [79][80][81]. Surprisingly, the strength of gene flow within the P. mugo complex is not consistent considering the genetic relatedness between the taxa-in fact, P. mugo and P. uncinata are characterized by the lowest reciprocal migration rates among all analyzed species.…”
Section: Interspecific Gene Flowmentioning
confidence: 69%
See 1 more Smart Citation
“…Our data indicate that the pattern of introgression is not symmetric between taxa, and in general, stronger gene flow was estimated from representatives of the P. mugo complex to P. sylvestris than in the opposite direction. Earlier studies reported such asymmetric ongoing gene flow within present-day contact zones of P. uliginosa, P. mugo, and P. sylvestris [79][80][81]. Surprisingly, the strength of gene flow within the P. mugo complex is not consistent considering the genetic relatedness between the taxa-in fact, P. mugo and P. uncinata are characterized by the lowest reciprocal migration rates among all analyzed species.…”
Section: Interspecific Gene Flowmentioning
confidence: 69%
“…The wide distribution of P. sylvestris and its known long-distance migration associated with postglacial recolonization of Europe could facilitate overlap with other pine species and locally restricted gene flow. Previous studies reported similarities between Scots pine populations from Poland and Finland [85,86], reflecting their common phylogeographic history, and mitotype sharing between P. uliginosa, P. mugo, and P. sylvestris in their contact zones was also reported [33,80].…”
Section: Interspecific Gene Flowmentioning
confidence: 82%
“…Another species recorded in these phytocoenoses is subalpine Pinus mugo Turra and its hybrids with P. sylvestris-P. x rhaetica (=P. uliginosa Neumann) [66,67]. The herb layer is composed of rare in the study area species of boreocontinental range type (Empetrum nigrum L., Vaccinium uliginosum).…”
Section: Discussionmentioning
confidence: 99%
“…Pinus sylvestris L. is widely distributed in Russia, Turkey, Mongolia, and the Greater Khingan Mountains Forest region of China. It has strong cold-resistance capability and does not require rich soil moisture conditions; thereby, it is capable for utilization as an afforestation tree species in mountainous and sand dune areas (Ekman et al 2002;Korkut et al 2008;Arriaga et al 2012;Cai et al 2016;Buyuksari et al 2017;Burawska-Kupniewska et al 2019;Sarkhad et al 2020;Sobierajska et al 2020). Pinus sylvestris L. has various apparent material performance, such as straight texture, clear pattern, moderate uniform structure, lightweight performance, low density, distinct rosin smell, high water resistance, high moisture resistance, good antifungal corrosion, and high durability, so it is mainly used in structural materials, and is also widely used in other wood production fields (Megnis et al 2002;Yildiz et al 2004;Rautiainen and Alen 2007;Temiz et al 2008;Simsek et al 2010;Bekhta et al 2014;Witomski et al 2014;Shen et al 2020).…”
Section: Methodsmentioning
confidence: 99%